If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1=4x-1/6x+7
We move all terms to the left:
1-(4x-1/6x+7)=0
Domain of the equation: 6x+7)!=0We get rid of parentheses
x∈R
-4x+1/6x-7+1=0
We multiply all the terms by the denominator
-4x*6x-7*6x+1*6x+1=0
Wy multiply elements
-24x^2-42x+6x+1=0
We add all the numbers together, and all the variables
-24x^2-36x+1=0
a = -24; b = -36; c = +1;
Δ = b2-4ac
Δ = -362-4·(-24)·1
Δ = 1392
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{1392}=\sqrt{16*87}=\sqrt{16}*\sqrt{87}=4\sqrt{87}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-36)-4\sqrt{87}}{2*-24}=\frac{36-4\sqrt{87}}{-48} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-36)+4\sqrt{87}}{2*-24}=\frac{36+4\sqrt{87}}{-48} $
| x/5+x/4=20 | | 125m-75m+47500=51250-200m | | 10/1=(0.18+x)/(0.1-x) | | 4x+1/3=81/3 | | 60+50.45x=57095x | | -6x-7.4=10.6 | | 19+x/4=31 | | 3-6v =45 | | 10+9(2x+4)=8-x | | -11=-2x-9 | | h−2=8 | | 5x+6(3x+2)=-57 | | 3=c−8 | | 2c+2=6c-4 | | 97n=194 | | 97=n+45 | | 8x-1=63 | | 23+n=65 | | 8n+1=25 | | +14x+4=16x+10 | | f−6=4 | | 63=3n | | 0.4+n/3=1 | | (6x-2)+20=180 | | 2x-2=10x=4 | | 4+3(-q)=10 | | -4x+1.75=13.75 | | 3y+5(y+4)=4y-2(y-10) | | -4(1x-2)=3(1x+5) | | 2.1/42=7;t | | 21x+99=21+18 | | -8w+24=-6(w-2) |